6(y-1)-4=-4(-6y+3)-4y

Simple and best practice solution for 6(y-1)-4=-4(-6y+3)-4y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(y-1)-4=-4(-6y+3)-4y equation:


Simplifying
6(y + -1) + -4 = -4(-6y + 3) + -4y

Reorder the terms:
6(-1 + y) + -4 = -4(-6y + 3) + -4y
(-1 * 6 + y * 6) + -4 = -4(-6y + 3) + -4y
(-6 + 6y) + -4 = -4(-6y + 3) + -4y

Reorder the terms:
-6 + -4 + 6y = -4(-6y + 3) + -4y

Combine like terms: -6 + -4 = -10
-10 + 6y = -4(-6y + 3) + -4y

Reorder the terms:
-10 + 6y = -4(3 + -6y) + -4y
-10 + 6y = (3 * -4 + -6y * -4) + -4y
-10 + 6y = (-12 + 24y) + -4y

Combine like terms: 24y + -4y = 20y
-10 + 6y = -12 + 20y

Solving
-10 + 6y = -12 + 20y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-20y' to each side of the equation.
-10 + 6y + -20y = -12 + 20y + -20y

Combine like terms: 6y + -20y = -14y
-10 + -14y = -12 + 20y + -20y

Combine like terms: 20y + -20y = 0
-10 + -14y = -12 + 0
-10 + -14y = -12

Add '10' to each side of the equation.
-10 + 10 + -14y = -12 + 10

Combine like terms: -10 + 10 = 0
0 + -14y = -12 + 10
-14y = -12 + 10

Combine like terms: -12 + 10 = -2
-14y = -2

Divide each side by '-14'.
y = 0.1428571429

Simplifying
y = 0.1428571429

See similar equations:

| 2y+2(y-8)=6y-4(y-10) | | 8x^2+16x=192 | | 39q+19+30=44q+45 | | 0=-16t^2+150t+30 | | x^2-49x+500=0 | | 6a-47+30=5a | | y+3-2(-8y-3)=7(y-1) | | 3.8x-4.7=3.8x+17.5 | | 19-12x=151 | | 2a+36=4a-14 | | 2.67x+3x=102 | | (x-2)2+(y-4)2=36expand | | 5x+10=-26 | | 34616.0131=B*45.3 | | ln(4x)+1=3 | | (v+39)+5v=11v-36 | | 3679.6530=171.9464*h | | 5k-12=-22 | | -4x-16=-33 | | cbrt(x)+cbrt(x-16)=cbrt(x-8) | | 1378384.64=4534.16*h | | (x-2)2+(y-4)2=36 | | g(p+3)=2x^2+5x+2 | | 9x-5=32 | | 7(x-3)=(4x+5) | | (2k-1)x^2-7x+(k+9)=0 | | 8a-28+3a=9a | | 22(x-5)+1x=-11-(x-1) | | 2a-19=7a+31 | | 6a-5a=13 | | 12p-16=-44+16p | | (p*p*p)-(1p*2p)=(p*p)+40p |

Equations solver categories